Efektivitas Sanksi Pidana terhadap Orang Tua Pecandu Narkotika yang Tidak Melapor Anaknya Ke Kepolisian Resor Tanjung Jabung Timur - Mhd. Badri; Sumaidi Sumaidi; Reza Iswanto (Universitas Batanghari Jambi, 2023)
Currently, many children are addicted to narcotics, so the role of parents is needed in reporting their children if they use narcotics to the authorities, including the Tanjung Jabung Timur Resort Police. This research is of the juridical empirical type which is carried out directly to the field using a socio-legal research approach. For data sources, it was carried out directly in the field by direct interviews with informants and library research was also carried out by means of document studies so that the data analysis used was qualitative analysis. The results of this discussion are related to the effectiveness of criminal sanctions against parents of narcotics addicts who do not report their children to the East Tanjung Jabung Resort Police, namely that the criminal sanctions have not been effective and efforts to make these criminal sanctions effective, the East Tanjung Jabung Police continue to socialize related parents with the criminal sanction.